Glucose Transporters in Sex Steroid Hormone Related Cancer - Nualart, Francisco; Garcia, Maria de los Angeles; Medina, Rodolfo A.; Owen, Gareth I. (Current Vascular Pharmacology, 2009)
Cancer cells, as with most mammalian cells, depend on a continuous supply of glucose; not only as a precursor of glycoproteins, triglycerides and glycogen, but also as an important source of energy. This review concentrates on GLUT transporter expression in both normal and cancerous classical sex-steroid hormone tissues (i.e. breast, uterus, ovary, testis and prostate, among others). Given the importance of estrogen, progesterone and androgens in carcinogenesis, as well as in survival and propagation of these cancers, this review also highlights the current literature on hormone regulation of glucose transporters and on the role of hypoxia in their expression. Furthermore, the recent explosion of information on the newer GLUT6-12 family members, a brief overview on their function and general expression has been included. Finally, an insight into the use of glucose transporters as markers of cancer progression and clinical outcome is also discussed.
Keywords: uterus